On the describing function method and the prediction of limit cycles in nonlinear dynamical systems - Azenha, Abílio (2016)
This paper analyses the limit cycle characteristics of systms with nonlinear friction or dynamics backlash. The study is based on the describing function (DF) of nonlinear systems being the nonlinear blocks composed on a mass subected to nonlinear friction or two masses subjected to backlash. the rehability of the method is analysed through the extended harmonic content of the systems DFs and using the Nyquist plot of the dynamic response used in the DFs calculations. The overall systems performance is tested using classical PID controllers.